Psychological Distress during Ovarian Cancer Treatment: Improving Quality by Examining Patient Problems and Advanced Practice Nursing Interventions - Cynthia Kline O'Sullivan; Kathryn H. Bowles; Sangchoon Jeon; Elizabeth Ercolano; Ruth McCorkle (Nursing Research and Practice)
Background/Significance. Ovarian cancer patients are prone to psychological distress. The clinical significance and best practices for distress among this population are poorly understood. Method. Secondary analysis of research records from a six month randomized control trial included 32 women with primary ovarian cancer. All received 18 advanced practice nurse (APN) visits over six months. Three sub-samples were determined by distress level (high/low) and mental health service consent for high distress. Demographic, clinical factors, patient problems and APN interventions obtained through content analysis and categorized via the Omaha System were compared. Results. Clinically-significant psychiatric conditions were identified in 8/18 (44%) high distress subjects consenting to mental health intervention. High distress subjects who refused mental health intervention had more income and housing problems than the other subjects, received the fewest interventions at baseline, and progressively more throughout the study, exceeding the other sub-samples by study completion. Conclusions. Highly-distressed women not psychologically ready to work through emotional consequences of cancer at treatment onset may obtain support from APNs to manage cancer problems as they arise. Additional studies may identify best practices for all highly-distressed women with cancer, particularly those who do not accept mental health services for distress, but suffer from its effects.